Pengaruh Penggunaan Pupuk Cair Daun Kelor dengan Penambahan Kulit Buah Pisang Terhadap Pertumbuhan Tanaman Jagung - Susila, Shofiatin; Asngad, M.Si, Dra.Aminah Asngad, M.Si (2016)
The organic fertilizer is one of the additional material that can be sufficient nutrients needed by plants. Organic fertilizers can be made of various materials such that Moringa leaves and banana peels. The use of such materials can maximize the benefits of Moringa leaves and banana peels. This study aimed to determine the effect of liquid fertilizer use moringa leaves with banana peel on the growth of corn plants with watering intervals and different concentrations. The method used is experiment with the design of experiments using two factors. Factor one is watering intervals, I1: 3 days, I2: 4 days and I3: 5 days. Factor two: fertilizer, P1: 40% fertilizer, P2: 50% of fertilizers and P3: 60% fertilizer. The study was conducted with two replications and the data obtained by observation during 4 weeks. After analysis using ANOVA showed that fertilizer Moringa leaves and banana peels to the time interval watering and different concentrations give effect to the high corn stalks and broad leaves. A comparison of the shows that treatment I1P2 (watering three days with 50% fertilizer) is the treatment of the most significant on high corn stalks and broad leaves.